ЛАБОРАТОРНІ ПРЕДИКТОРИ ДЛЯ ДІАГНОСТИКИ / НЕСПРОМОЖНОСТІ КОЛОРЕКТАЛЬНОГО АНАСТОМОЗУ - GORDIICHUK, M.; MYASOYEDOV, S. (PH Akademperiodyka, 2024)
Background. An important concern in oncological coloproctology is colorectal anastomotic leakage (AL), which occurs in 3.5%–21% of patients. Predicting the occurrence of failure based on the results of laboratory markers can be decisive for the treatment of this complication. Aim. To improve the early diagnosis of AL by establishing combinations and threshold values of laboratory markers — predictors of the inflammatory process. Materials and Methods. The prospective study, conducted from 2020 to 2023, included 213 rectal cancer patients who underwent low anterior resection after neoadjuvant chemoradiotherapy. The inflammatory biomarkers were assessed before surgery and on the 3rd, 5th, and 7th days of the postoperative period. Results. AL diagnosed in 25 (11.74%) patients by the grade of severity was as follows: A (radiological) in 7 (3.29%) patients; B (clinical) — 4 (1.88%); C (clinically expressed, peritonitis) — 11 (5.16%), and P (late) — 3 (1.41%) patients. The changes in the laboratory indicators of the inflammatory response such as С-reactive protein (CRP), procalcitonin (PCT), the counts of neutrophils (NEU), lymphocytes (LYM), platelets (PLT), and neutrophil/lymphocyte ratio (NLR) were significant only in B or C AL grades. Among them, only three indicators were identified as significant for predicting AL when assessed 24 h before the onset of this complication, namely LYM (threshold value ≤ 0.97 × 103/mm3, sensitivity 66.7% and specificity 81.3%, p < 0.001); PLT (threshold value > > 257 103/mm3, sensitivity 58.6%, and specificity 86.7%, p < 0.001); and NLR (threshold value > 4.42, sensitivity 58.1%, and specificity 86.7%, p < 0.001). The three-factor model based on these selected indicators was set up, and the prognosis index (Prog) was proposed with the decision threshold Progcrit = 2.23. The sensitivity of the model was 80% (95% CI 51.9%—95.7%), and the specificity — 74.2% (67.6%—80.2%). Conclusion. Based on the routine laboratory predictors used in the complex diagnosis of AL, B or C AL grades may be predicted allowing for the timely effective early diagnosis, medication, and surgical intervention..